Comparison study of schemes for separation of intermediate isotope components. Issue 12 (12th August 2020) - Zeng, Shi; Smirnov, A.Yu.; Borisevich, V.D.; Sulaberidze, G.A.
ABSTRACT: This paper uses the Q-cascade model to investigate the separation performance of eight schemes, comprising variations of two single-cascades and two double-cascades, to separate an intermediate isotope component. Optimization determines the relationship between the minimum relative total flow and concentration for different concentration requirements of the intermediate component. The results show that single-cascade schemes are not efficient. Rather, the optimal scheme is a double-cascade scheme that uses a three-stream cascade and a cascade with two feeds and an intermediate withdrawal. The successful optimization of all schemes indicates that this approach can be generalized to optimize various multistep separation processes.